2013
DOI: 10.1111/jace.12359
|View full text |Cite
|
Sign up to set email alerts
|

Novel Series of Low‐Firing Microwave Dielectric Ceramics: Ca5A4(VO4)6 (A2+ = Mg,Zn)

Abstract: Using a conventional solid-state reaction Ca 5 A 4 (VO 4 ) 6 (A 2+ = Mg, Zn) ceramics were prepared and their microwave dielectric properties were investigated for the first time. X-ray diffraction revealed the formation of pure-phase ceramics with a cubic garnet structure for both samples. Two promising ceramics Ca 5 Zn 4 (VO 4 ) 6 and Ca 5 Mg 4 (VO 4 ) 6 sintered at 725°C and 800°C were found to possess good microwave dielectric properties: e r = 11.7 and 9.2, Q 3 f = 49 400 GHz (at 9.7 GHz) and 53 300 GHz (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(23 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Studies have shown that ε r generally depends on porosity, microstructure, polarizability, and the secondary phase . The corrected dielectric constant values ( ε corr ) were used in the following equation:εnormalr=εcorr1-3Pεcorr-12εcorr+1.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that ε r generally depends on porosity, microstructure, polarizability, and the secondary phase . The corrected dielectric constant values ( ε corr ) were used in the following equation:εnormalr=εcorr1-3Pεcorr-12εcorr+1.…”
Section: Resultsmentioning
confidence: 99%
“…(e)], and EDS [Fig. (c)] analysis results, the deterioration in microwave dielectric properties of MZTS–CST–6.8LFV ceramics could be due to the residual liquid phase as well as secondary phase Ca 5 Mg 4 (VO 4 ) 6 (ε r = 9.2, τ f = −50 ppm/°C) . Based on the above data therefore, MZTS–CST–5.3LFV composite ceramic sintered at 950°C possesses optimum microwave dielectric properties of ε r = 16.3, Q × f = 30 790 (at 8.3 GHz), and τ f = −10 ppm/°C.…”
Section: Resultsmentioning
confidence: 74%
“…In our previous work, the Ca 5 A 4 (VO 4 ) 6 (A = Mg, Zn, Co) ceramics sintered at below 900°C exhibited good microwave dielectric properties [11,12]. Mn 2?…”
Section: Introductionmentioning
confidence: 94%